Life time improvement with hybrid clustering in Mobile Sensor Networks - Suma, G; Siddappa, M (International Journal of Computer Sciences and Engineering, 2025)
In mobile sensor networks (MSN) handling dynamically changing topology in clustered MSNs is an important challenge as it affects the cluster formation. If re cluster triggering is performed at predetermined time or rounds without considering nodes position and stability of original cluster structure, leads to unnecessary energy usage in a dynamic topology. Life time of MSN can be extended by efficient re cluster triggering techniques. In this work cluster head (CH) rotation and re cluster triggering carried out either locally or globally based on changing position of CH and backup-CH (BU-CH) or residual energy. CH, one BU-CH are identified in every cluster, CH hands over its role to BU-CH without altering cluster structure in case it moves out of cluster boundary. In the absence of both within core boundaries then either local or global re clustering triggered. Reclustering and CH rotation are triggered when CH or BU-CH nodes surpass their boundaries and not by predetermined time or rounds as in most works. This work is a hybrid, distributed, topology driven clustering technique with minimum overheads, reduced reclustering in turn prolongs network lifetime.